Reologicheskie cvoistva krovi u sportsmenov raznoi kvalifikatsii - Vikulov, A. D. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The purpose of this research was to study the rheological properties of blood in athletes. 36 athletes of various qualification acted as subjects of that research. The athletes were in the peak of sports form and they had been tested in the middle of the competitive period. The main hemorheological parameter revealed in the research was the deformations of erythrocytes. The hemorheological displacements had been registered on the background of stable indexes of the systolic and diastolic arterial pressure and the bradycardia.